PROSES PERENCANAAN WISATA SWAFOTO DI DESA WANAGIRI, BULELENG, BALI - Made Sanjaya; I Komang Gede Santhyasa (UNHI PRESS, 2020)
This study aims to understand in depth the process of selfie tourism planning in the Village of Wanagiri. Through a tourism destination life cycle approach, the selfie tourism planning process is identified from three actors and interests. First, the ruler / government; Second, experts / planners / planning experts; and Third, the community or stakeholders. Each of the four planning process approaches differs in who or who most dominates the planning process. This research uses a qualitative research approach by taking the case study of Wanagiri Village as the object of research. Data obtained purposively to the village of Wanagiri, BKSA and local communities. Data analysis was performed using evaluative-prescriptive techniques. In the end, this study found that the process of selfie tourism planning in Wanagiri Village used a Participatory planning approach. The planning process from the discovery stage to the stage of developing selfie tourism in the village of Wanagiri is still carried out independently, through consultation and initiation by the local community.